Report on research, innovation and technological performance in Germany 2016 - EFI - Commission of Experts for Research; Innovation (Commission of Experts for Research and Innovation (EFI), 2016)
[Foreword] In its analyses and recommendations the 2016 Report of the Commission of Experts for Research and Innovation addresses current developments (A chapters), presents a series of detailed studies (B chapters), and documents the development of Germany's research and innovation system on the basis of eight groups of indicators (C chapters). [...] The Commission of Experts reiterates its assessment that digitisation, connectedness and the introduction of new internet-based business models cause disruptive changes. In the light of the experience gained in the 1980s, it is confident that Germany can do well when it comes to making the necessary adjustments to the labour market. Overall, however, German political decision-makers are currently too intent on defending established German strengths. The creative possibilities of digitisation are not being given sufficient consideration. In future, Germany needs to be more involved in opening up new sources of value creation and jobs - this will also require some rethinking among political decision-makers.
Keywords: 330